All of us the collected poems - Carver, Raymond 1938-1988 (Knopf, 1998)
The collected poems of a native of Oregon. In Venice, he writes: "The gondolier handed you a rose. Took us up one canal and then another. We glided past Casanova's palace, the palace of the Rossi family, palaces belonging to the Baglioni, the Pisani, and Sangallo. Flooded. Stinking."